Agendamento online para salão de beleza - ROSENO, Camila; ALVES, Caroline; FERNANDEZ, Letícia; LIMA, Mariana; CRISTINA, Zaine (166, 2013)
-
Keywords: Softwares; Estética (Serviços); Informação e Comunicação